From Backpain to Paraplegia: A Rare Primary Presentation of Metastatic Ovarian Cancer in Pregnancy - Filiz Çayan; Arzu Doruk; Aslı Köseoğlu; Mutlu Alımlı; Leyla Cinel; Saffet Dilek (Medical Network, 2011)
Vertebral metastasis from epithelial ovarian carcinoma is extremely rare and usually diagnosed at autopsy. We present here an unusual case of pregnant woman who developed paraplegy, due to thoracal vertebral metastasis and pathologic vertebral fracture of ovarian carcinoma.